Cheirostylis barbata, a new species Orchidaceae (Goodyerinae) from Yunnan, China - Wu, Xun-Feng; Liu, Qiang; Li, Jin-Long; Tang, Zong-Ying; Xing, Xiao-Ke (Phytotaxa, 2020)
Cheirostylis barbata, a new species of Orchidaceae, is described and illustrated from Yunnan Province, China. It is morphological similar to C. griffthii, but it can be easily distinguished from the latter in having densely villous inflorescence, floral bracts 1.2–1.4 cm, significantly longer than ovary, lobes of lip deeply laciniate with 7–9 divisions, each lacinae randomly oriented, 6.0–7.5 mm long, hypochile containing 2 callus, each callus 4-toothed. A preliminary assessment of extinction risk, according to the IUCN Red List Categories and Criteria, is also provided.